An Analysis of Errors in English Writing: A Case Study the Third Semester Students of UBSI - Lia Nurmalia; Cicih Nuraeni (JURNAL ARBITRER, 2021)
The objectives of this research are to know the errors in the third semester students' writing of Bina Sarana Informatika University and the most frequent error. It is concerned to the grammatical and semantic and substance errors. The data is analyzed by using James' theory in (Mungungu, 2010). The findings show that errors done by the students are spelling 50.9%, fragment 15.7%, punctuation 9.8%, adjective 3%, subject- verb agreement 3.9%, preposition 3.9%, capitalization 3.9%, tenses 2%, verb 2%, literal translation 2%. It can be concluded that the most frequent error is spelling. It because the students missed a letter, added more letter in a word, and exchange the letter. While In grammatical category, the most frequent error is fragment. It is because the most students do not put a subject in a sentence.